PENGEMBANGAN TEKNIK FERMENTASI DALAM MENINGKATKAN MUTU BIJI KAKAO (Theobroma cacao L) - Nur Alam; Muhardi Muhardi; Abdul Rahim; Gatot Siswo Hutomo; Syahraeni Kadir; Sakka Samudin; Chitra Anggraeni Salingkat; Eko Priyantono; Ponirin Ponirin; Diky Gunawan Suwiyono (Fakultas Pertanian, Universitas Tadulako, 2022)
The purpose of this research was to achieve a shorter fermentation technique for cocoa beans by using ethanol, acetic acid and coconut water to produce high quality cocoa beans. The research was conducted in Tunus village Pamona Pusalemba sub district Poso district of Central Sulawesi. Tunus is located about 300 kilometers from Palu, the capital of Sulawesi Tengah. The fermented cocoa beans were analyzed at Tadulako University’s Agroindustry Laboratory Faculty of Agriculture. The study used a Randomized Block design (RBD) with fermentation technique as the treatments i.e., 10 kg wet cocoa only (Box 1), 10 kg wet cocoa + 75 ml ethanol (Box 2), 10 kg wet cocoa + 75 ml acetic acid (Box 3), and 10 kg wet cocoa + 75 ml aged coconut water (Box 4). Each treatment had four replicates, thus in total there were 16 experimental units. The results showed that the addition of 75 ml ethanol in the fermentation process had the shortest fermentation time, with an average fermentation time of four days. The method also produced the best average water content and sensory tests such as of color, texture, aroma, and overall liking.